(untitled) (Education in the 21st Century, 2023)
The introduction of new management models in public education institutions is one of the primary and important factors that can be used to ensure the uninterrupted organization of the public education process and the quick and efficient solution of internal problems. In this article, we aim to highlight the need to use new educational models to solve the existing problems in RA public education institutions and the effectiveness of new management models in solving a number of management and educational problems in RA public education institutions. This article presents a fresh perspective on the current foundations supporting the implementation of new management models with in the public education sector of RA, along with an overview of the recent and past efforts undertaken by relevant authorities to address these issues. Based on our research conducted in accordance with the RA Law ’On Public Education’ and relevant field studies, we can confidently assert that the implementation of new management models in the realm of public education will indeed prove to be effective.